Pressure Swing Adsorption Based Air Filtration/Purification Systems for NBC Collective Protection - Singh, Beer; Singh, Virendra V; Boopathi, M; Shah, D (Defence Life Science Journal, 2016)
The respiratory protection against chemical warfare agents (CWA) has become a worldwide security concern in light of the many recent international threats utilising CWA. Till date the carbon filtration was adequate to protect the soldiers from the threats of CWA. With the advent of further advancements in the CWA a new threat is looming large that is known as the carbon breakers. pressure swing adsorption (PSA) is a well-established gas separation technique in air separation, gas drying, and hydrogen purification separation. Recently, PSA technology has been applied in the area of chem-bio defence by virtue of its unique advantages. This article reviews recent advances and developments in the field of PSA based purification, separation, and its use in defense sector. This emerging and advanced PSA technology can provide regenerative nuclear, biological and chemical (NBC) collective protection for ground vehicles, aircraft, ships and shelters. This PSA technology challenges threat scenario developed which includes nerve, blood and blister agents, as well as a “carbon breaker” agent, and proved that this technology will be a viable concept for future NBC collective protection systems. New technological breakthroughs and greater sophistication of PSA technologies will transform the collective protection based PSA technology in real field sense, addressing the escalating threat of CWA. We conclude this review with future prospects and challenges associated with PSA technology.